2017
DOI: 10.1371/journal.pone.0170421
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopically Assisted Anorectal Pull-Through versus Posterior Sagittal Anorectoplasty for High and Intermediate Anorectal Malformations: A Systematic Review and Meta-Analysis

Abstract: ObjectiveAnorectal malformations (ARMs) are one of the commonest anomalies in neonates. Both laparoscopically assisted anorectal pull-through (LAARP) and posterior sagittal anorectoplasty (PSARP) can be used for the treatment of ARMs. The aim of this systematic review and meta-analysis is to compare these two approaches in terms of intraoperative and postoperative outcomes.MethodsMEDLINE, Embase, Web of Science and the Cochrane Library were searched from 2000 to August 2016. Both randomized and non-randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 40 publications
1
36
0
6
Order By: Relevance
“…The surgical management of RP following PSARP or LAARP for ARM remains a matter of discussion [ 5 , 9 , 10 ]. While in 2014, RP was stated to occur with a higher incidence after LAARP compared to PSARP [ 11 ], a recent meta-analysis showed that RP occurs with an incidence of 17.7% after LAARP and 12.8% after PSARP with no statistically significant difference between these two groups [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of RP following PSARP or LAARP for ARM remains a matter of discussion [ 5 , 9 , 10 ]. While in 2014, RP was stated to occur with a higher incidence after LAARP compared to PSARP [ 11 ], a recent meta-analysis showed that RP occurs with an incidence of 17.7% after LAARP and 12.8% after PSARP with no statistically significant difference between these two groups [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Newcastle–Ottawa Scale (NOS) was used to evaluate the study quality. [ 27 ] Adequacy of case definition, representativeness of the cases, selection of controls, definition of controls, comparability cases/controls, comparability cases/controls, same method of ascertainment, and non-response rate were taken into account and given a corresponding score. Total score ranged from 0 (lowest quality) to 8 (highest quality).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. 28 Two authors searched the databases PubMed, Embase, China National Knowledge Infrastructure (CNKI), Wanfang and Cochrane Library using the following terms: “Estrogen receptor 2”, “ESR2”, “Human epidermal growth factor receptor 2”, “HER2”, “polymorphism”, “single nucleotide polymorphism”, “SNP”, “ovarian cancer” and “ovarian carcinoma” up to July 1, 2017. There was no limitation in language.…”
Section: Methodsmentioning
confidence: 99%